PENGARUH PENGALAMAN MAGANG, SOFT SKILL, DAN MINAT KERJA TERHADAP KESIAPAN KERJA - Simanjuntak, Aristawin Raulina; Armanu, Armanu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to explain the effects of internship experience, soft skills, and work interest on the work readiness of the students of Faculty of Economics and Business of Universitas Brawijaya. Using probability sampling method and simple random sampling technique, 220 people were selected as the respondents. The data of this explanatory research was harvested from Likert-scaled questionnaires and was analyzed in SPSS version 25. This study finds that (1) internship experience positively and significantly influences the students’ work readiness, (2) that soft skills positively and significantly affect the students’ work readiness, and (3) that work interest positively and significantly impacts the students’ work readiness. Furthermore, it was found that, based on the coefficient of determination values, internship experience, soft skills, and work interest influence 58.7% of the work readiness of the students of Faculty of Economics and Business of Universitas Brawijaya.